Sleep Apnea Recent Updates - Vats, Mayank G. (IntechOpen, 2017)
Sleep medicine is developing rapidly with more than 100 sleep disorders discovered till now. Despite that, sleep specialty is in neonatal stage especially in developing and underdeveloped countries. Sleep medicine is still evolving with ongoing worldwide clinical research, training programs, and changes in the insurance policy disseminating more awareness in physicians and patients. Sleep apnea is one of the most common sleep disorders, found in around 5-7 % of the general population with high prevalence in the obese, elderly individuals but largely unrecognized and hence undiagnosed with untreated and life-threatening consequences. In the last decade, new complex sleep disorders and their pathophysiology have been discovered, new treatment options (pharmacological and nonpharmacological) are available, and hence we planned a book on the recent developments on the most common sleep disorder, sleep apnea. We have incorporated chapters from the eminent clinicians and authors around the globe to produce a state-of-the-art book with the target audience from internal medicine, pulmonary, sleep medicine, neurology, ENT, and psychiatry discipline.